(untitled) (Journal of Medicine, 2026)
Dengue fever is a mosquito-borne viral disease transmitted by Aedes mosquitoes particularly Aedes aegypti. There are 4 distinct serotypes (DEN1, DEN2, DEN3, and DEN4) causing dengue fever. The clinical manifestations of dengue fever are variable- fever, headache, body ache, retro-orbital pain, rash, & joint pain. It has a wide range of clinical manifestations, ranging from asymptomatic disease to a more complicated form -dengue hemorrhagic fever or dengue shock syndrome (DHF/DSS), which is characterized by increased vascular permeability, thrombocytopenia (platelets <100,000 units), bleeding tendency, and sometimes circulatory shock. Atypical manifestations, such as central nervous system, renal, and cardiac involvement, are increasingly being reported. Bleeding manifestations in dengue are well known, but thrombotic events are uncommon. Only a few case studies have previously documented the effects of dengue fever on the cardiovascular system, including conduction abnormalities, hypotension, arrhythmias, myocarditis, cardiomyopathy, and, infrequently, myocardial infarction. Some cardiac manifestations in dengue hemorrhagic fever, such as atrioventricular blocks, sinus node dysfunction, and ectopic ventricular beats, are noticed. The separation between myocarditis and myocardial infarction is necessary, for which echocardiography and coronary angiography can be helpful. ST-elevation myocardial infarction during dengue is rare but poses an important management dilemma. We present three patients with dengue fever with ST elevation myocardial infarction, and our experience in the management of those patients. We suggest individualized case-based management of acute coronary syndrome in dengue, which should be guided by the degree of thrombocytopenia, bleeding risk & comorbidities. J MEDICINE 2026; 27(1): 49-54